Parental Incarceration and Within-Individual Changes in Criminal Justice Involvement Across Developmental Stages - Silver, Ian A. (Journal of developmental and life-course criminology, 2023)
The current study examines the association between parental incarceration and the change in the number of arrests and number of months incarcerated across three life-course periods. Examining individuals’ involvement in the criminal justice system throughout the life-course is a well-documented area of research in criminology. However, limited research has examined how factors such as parental incarceration shape criminal justice involvement across different key life-course stages. To conduct the current study, we employed the National Longitudinal Survey of Youth-1997 (NLSY97) and used conditional piecewise latent growth models. The NLYS97 is a nationally representative dataset of individuals born in the United States between 1980 and 1984. We evaluated whether parental incarceration (before 16)—both paternal and maternal—influences within-individual changes in the number of arrests and months incarcerated between 17 and 25 years (late-adolescence), 26 and 30 years (early-adulthood), and 31 and 35 years (adulthood). The results show that parental incarceration differentially influences the change in the number of arrests and number of months incarcerated across the three life-course periods. Moreover, the magnitude and direction differ by the parent incarcerated and the race of the participant. The findings suggest that factors associated with parental incarceration might be associated with differential effects on criminal justice involvement across key life-course periods. To reduce the likelihood of CJS involvement as adolescents age into adulthood, interventions should be implemented to protect children from the social, economic, and health-related harms of having a parent go to prison.